Alumina feed material and preparation method and application thereof
By improving the formulation and preparation process of alumina feeding and adopting a three-step mixing process in stages, the existing alumina feeding has solved the shortcomings in powder loading, density, fluidity and cost, and achieved high performance and High yield alumina ceramic products.
Patent Information
- Application Number
- CN202310063986.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The existing alumina feeding has shortcomings in powder loading, density, fluidity, shrinkage and cost, resulting in poor mechanical properties and low yields of ceramic products.
By improving the formulation and preparation process of alumina feeding, alumina ceramic powder and binder including solid modifier, skeleton agent and form-keeping agent are used to mix in three stages to increase the powder loading, density and Liquidity, reduce shrinkage and cost.
High powder loading (70-85%), high density (3.92-3.95g/cm3), high fluidity (500-1400g/10min), low shrinkage (1.198-1.208%) and low cost alumina Feeding, the produced alumina ceramic products have good mechanical properties (flexural strength 310-380MPa, hardness 1720-1830kgf/mm2) and high yield (85-91%).
Smart Images

Figure CN116102341B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of powder metallurgy, and more specifically, to an alumina feed material and a preparation method and application thereof. Background Art
[0002] Alumina is a high-hardness, high-strength and insulating material that is widely used in aerospace, new energy and semiconductor fields. However, alumina is difficult to process, which increases the cost of post-processing and limits its application. Ceramic powder injection molding (CIM) technology uses a binder mixed with alumina ceramic powder to form an alumina feed with a certain fluidity, which is then injected into the mold, degreased and sintered to achieve the purpose of near-net molding of alumina ceramic products, greatly improving the structural variability of alumina ceramic products and reducing overall costs.
[0003] At present, for the alumina injection molding process, wax-based alumina feedstock (i.e., using wax-based binders) and plastic-based alumina feedstock (i.e., using plastic-based binders) have been developed. Wax-based alumina feedstock cannot meet the requirements of large-scale stable mass production in modern industry. Although plastic-based alumina feedstock can be mass-produced, it generally faces the problems of difficult mixing, easy decomposition, large shrinkage rate, and high cost. It has high requirements for powder quality and needs to use spherical ceramic powder. There are problems such as high cost, difficulty in sintering, small particle size, and difficulty in uniform dispersion of powder, resulting in low powder loading (about 65-76%), difficult mixing of feedstock, and poor mechanical properties of ceramic products after sintering of feedstock (flexural strength is generally 250-280MPa, density 3.85-3.90g / cm 3 ); and the poor fluidity of the traditional plastic-based alumina feedstock (melt flow rate is generally 200-600g / 10min), which leads to cracking or hidden cracks in the material after injection molding and degreasing, resulting in low product yield and high potential risk. Therefore, it is urgent to develop a plastic-based alumina feedstock with high powder loading, easy mixing, high fluidity and low cost to meet the requirements of the alumina ceramic powder injection molding process, with good mechanical properties and high yield after sintering. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides an alumina feed material and a preparation method and application thereof. The present invention improves the formula and preparation process of the alumina feed material to obtain an alumina feed material with high powder loading (70-85%), high density (3.92-3.95 g / cm 3), easy to mix, high fluidity (melt flow rate 500-1400g / 10min at 190℃ and 21.6kg), low shrinkage (1.198-1.208%), low cost, the obtained alumina ceramic products have good mechanical properties (bending strength 310-380MPa, hardness 1720-1830kgf / mm 2 ), high product yield (85-91%).
[0005] A first aspect of the present invention provides a method for preparing an alumina feed material.
[0006] Specifically, a method for preparing an alumina feedstock, wherein the raw materials for preparing the alumina feedstock include alumina ceramic powder and a binder, wherein the binder includes a solid modifier, a skeleton agent and a shape retaining agent;
[0007] The method for preparing the alumina feed material comprises the following steps:
[0008] (1) mixing alumina ceramic powder and a solid modifier, and performing a first kneading to obtain material A;
[0009] (2) mixing the material A obtained in step (1) with the skeleton agent, and performing a second mixing to obtain material B;
[0010] (3) Mixing the material B obtained in step (2) with a shape retaining agent, performing a third mixing process, and granulating to obtain the alumina feed material.
[0011] The present invention first mixes the alumina ceramic powder and the solid modifier for the first mixing. The solid modifier is melted and coated on the surface of the alumina ceramic powder to form a lubricating layer, thereby improving lubricity, reducing the frictional heat between the powders during subsequent mixing and causing the feed to decompose, and at the same time, deagglomerating the powder, improving the powder dispersion, and facilitating sintering dimensional stability and uniform composition. The purpose of the second mixing is to form a coupling effect between the groups of the surface layer formed by the solid modifier added in the first mixing after the framework agent is melted, thereby enhancing the strength of the blank after subsequent catalytic degreasing and avoiding cracking. The purpose of the third mixing is to use a shape retaining agent to give the feed good formability. The present invention improves the affinity between the alumina ceramic powder and the solid modifier, the framework agent, the shape retaining agent and other binders through three-step mixing and molding in stages, so that the internal structure of the alumina feed has a hierarchical structure. In the subsequent process stages, the components can play a synergistic role, reduce the cost of raw materials, and greatly reduce the decomposition risk of the feed during the preparation process.
[0012] Preferably, in step (1), the mass of the alumina ceramic powder accounts for 70-85% of the total mass of the alumina feed material.
[0013] More preferably, in step (1), the mass of the alumina ceramic powder accounts for 77-82% of the total mass of the alumina feed material.
[0014] Powder loading is the mass percentage of alumina ceramic powder to the total mass of alumina feed.
[0015] Preferably, the mass content of aluminum oxide in the aluminum oxide ceramic powder is 90-100%.
[0016] More preferably, the mass content of aluminum oxide in the aluminum oxide ceramic powder is 95-100%.
[0017] Further preferably, the mass content of aluminum oxide in the aluminum oxide ceramic powder is 99.7-100%.
[0018] Preferably, the particle size of the alumina ceramic powder is 0.8-1 μm.
[0019] Preferably, the alumina ceramic powder is a non-spherical powder.
[0020] Preferably, the mass of the binder accounts for 15-30% of the total mass of the alumina feed.
[0021] More preferably, the mass of the binder accounts for 18-23% of the total mass of the alumina feed.
[0022] Preferably, the binder further comprises a lubricant and / or a liquid modifier.
[0023] Preferably, the addition of the shape retaining agent also includes the addition of a lubricant and / or a liquid modifier, so as to further increase the fluidity and demoulding effect of the feed material.
[0024] Preferably, the mass of the solid modifier accounts for 1-3% of the total mass of the binder.
[0025] Preferably, the mass of the skeleton agent accounts for 9-11% of the total mass of the binder.
[0026] Preferably, the mass of the shape retaining agent accounts for 75-91% of the total mass of the binder.
[0027] Preferably, the mass of the lubricant accounts for 0-10% of the total mass of the binder.
[0028] Preferably, the mass of the liquid modifier accounts for 0-1% of the total mass of the binder.
[0029] Preferably, the solid state modifier is stearic acid (SA).
[0030] Preferably, the framework agent is polypropylene (PP) and / or polyethylene (PE).
[0031] Preferably, the polyethylene is high density polyethylene (HDPE).
[0032] Preferably, the shape retaining agent is polyoxymethylene (POM).
[0033] Preferably, the lubricant is paraffin wax (PW).
[0034] Preferably, the liquid modifier is oleic acid (OA).
[0035] Preferably, in step (1), the temperature of the first mixing is 180-190° C., and the time of the first mixing is 1-10 min.
[0036] More preferably, in step (1), the temperature of the first mixing is 185-190° C., and the time of the first mixing is 5-10 min.
[0037] Preferably, in step (1), the first mixing further comprises stirring, and the stirring speed is 10-30 rpm.
[0038] Preferably, in step (2), the temperature of the second mixing is 180-190° C., and the time of the second mixing is 10-30 min.
[0039] More preferably, in step (2), the temperature of the second mixing is 185-190° C., and the time of the second mixing is 10-20 min.
[0040] Preferably, in step (2), the second mixing further comprises stirring, and the stirring speed is 10-30 rpm.
[0041] Preferably, in step (3), the temperature of the third mixing is 180-190° C., and the time of the third mixing is 60-80 min.
[0042] More preferably, in step (3), the temperature of the third mixing is 185-190° C., and the time of the third mixing is 60-70 min.
[0043] Preferably, in step (3), the third mixing further comprises stirring, and the stirring speed is 30-40 rpm.
[0044] Preferably, in step (1), before mixing the alumina ceramic powder and the solid modifier, the alumina ceramic powder is also preheated, the preheating temperature is 120-140° C., and the preheating time is 15-45 minutes.
[0045] The alumina ceramic powder is first preheated to allow the surface of the alumina ceramic powder to be evenly heated, so that the subsequent solid modifier can be heated and melted and evenly coated on the surface of the alumina ceramic powder.
[0046] Preferably, the preheating further comprises stirring, and the stirring speed is 1-10 rpm.
[0047] A second aspect of the present invention provides an alumina feedstock.
[0048] An alumina feed material, wherein the melt flow rate of the alumina feed material at 190° C. and 21.6 kg is 500-1400 g / 10 min.
[0049] A third aspect of the present invention provides a use of an alumina feed material.
[0050] The invention discloses an alumina feed material for use in the fields of aerospace, new energy or semiconductor.
[0051] An alumina ceramic product. The raw materials for preparing the alumina ceramic product include the alumina feed material.
[0052] Preferably, the alumina ceramic product is made by a ceramic powder injection molding process.
[0053] Preferably, the ceramic powder injection molding process comprises the following steps:
[0054] The alumina feed material is injection molded, degreased, and sintered to obtain the alumina ceramic product.
[0055] Preferably, the sintering temperature is 1630-1700° C., and the sintering time is 2-5 hours.
[0056] Preferably, the flexural strength (σ) of the alumina ceramic product is greater than 310 MPa.
[0057] Preferably, the hardness (HV) of the alumina ceramic product is greater than 1720.
[0058] Alumina ceramic products have good mechanical properties.
[0059] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0060] (1) The present invention uses alumina ceramic powder and a binder as the main raw materials for preparing alumina feedstock, wherein the binder includes a solid modifier, a skeleton agent and a shape retaining agent. The alumina ceramic powder and the solid modifier are first mixed for the first mixing, the skeleton agent is added for the second mixing, and the shape retaining agent is added for the third mixing. After the three mixing and modification, the affinity between the polar surface groups of the alumina ceramic powder and the binder is improved, and the dispersion of the alumina feedstock is improved. The step-by-step mixing makes the layers of the components in the alumina feedstock orderly, the powder loading is as high as 70-85%, and the density can reach 3.92-3.95 g / cm 3 , high fluidity (melt flow rate at 190°C and 21.6kg is 500-1400g / 10min), low shrinkage (1.198-1.208%), can be well applied in the subsequent ceramic powder injection molding process to produce alumina ceramic products with good mechanical properties;
[0061] (2) The alumina feedstock prepared by the present invention is used to prepare alumina ceramic products, with good mechanical properties, a degreasing stage yield rate of 85-91%, stable and reliable performance, a bending strength of not less than 310 MPa, and a hardness of not less than 1720 kgf / mm 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a flow chart of the preparation method of Example 3 of the present invention. DETAILED DESCRIPTION
[0063] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0064] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0065] Example 1 (without adding liquid modifier)
[0066] A method for preparing an alumina feed material, wherein the raw materials for preparing the alumina feed material include 82wt% alumina ceramic powder and 18wt% binder, and the method for preparing the alumina feed material includes the following steps:
[0067] (1) Weigh alumina ceramic powder according to the powder loading amount of 82% (Al in alumina ceramic powder) 2 O 3 The content is 99.7%). Add it into the mixing chamber, set the temperature to 130°C for preheating, and the stirring speed (rotor speed) to 5 rpm;
[0068] (2) Add 1% of the mass of the binder as solid modifier SA, mix at a stirring speed of 20 rpm, and perform the first pressurization (i.e., compaction hammer) mixing at 185° C. for 10 min, the same below;
[0069] (3) Add 5% of the mass of the binder skeleton agent PP and 4% of the mass of the binder HDPE, mix at a stirring speed of 20 rpm, and perform a second pressurized mixing for 20 min to allow the powder and the binder to bond;
[0070] (4) Add 80% of the binder weight of POM as a mold retainer and 10% of the binder weight of PW as a lubricant, increase the stirring speed to 35 rpm, perform the third pressurized mixing for 60 minutes, and granulate to obtain alumina feed.
[0071] Example 2 (without lubricant or liquid modifier)
[0072] A method for preparing an alumina feed material, wherein the raw materials for preparing the alumina feed material include 82wt% alumina ceramic powder and 18wt% binder, and the method for preparing the alumina feed material includes the following steps:
[0073] (1) Weigh alumina ceramic powder according to the powder loading amount of 82% and add it into the internal mixing chamber. The content of alumina in the alumina ceramic powder is 99.7%. Set the temperature to 130° C. and the rotor speed to 5 rpm for preheating;
[0074] (2) Add 3% of SA by weight of the binder, stir at 20 rpm, heat to 185°C, and perform the first pressurized mixing for 10 min;
[0075] (3) Add 6% PP and 5% HDPE as binder by weight, stir at 20 rpm, and perform a second pressurized mixing for 20 min to bond the powder and the binder;
[0076] (4) POM with a mass percentage of 86% of the binder is added, and when the feed material forms continuous flocs, the rotor speed is increased to 35 rpm, and the third pressurized mixing is performed for 60 minutes. The feed material is extruded and granulated by a granulator to obtain an alumina feed material.
[0077] Example 3 (adding a mold retaining agent, a lubricant and a liquid modifier simultaneously)
[0078] A method for preparing an alumina feed material, wherein the raw materials for preparing the alumina feed material include 82wt% alumina ceramic powder and 18wt% binder, and the method for preparing the alumina feed material includes the following steps:
[0079] (1) Weigh alumina ceramic powder according to the powder loading amount of 82% and add it into the internal mixing chamber. The content of alumina in the alumina ceramic powder is 99.7%. Set the temperature to 130° C. and the rotor speed to 5 rpm for preheating;
[0080] (2) Add 3% of SA by weight of the binder, stir at 20 rpm, heat to 185°C, and perform the first pressurized mixing for 10 min;
[0081] (3) Add 6% PP and 5% HDPE as binder by weight, stir at 20 rpm, and perform a second pressurized mixing for 20 min to bond the powder and the binder;
[0082] (4) Add 75% of POM by weight of the binder, 10% of PW by weight of the lubricant, and 1% of OA by weight of the binder, and wait until the feed material forms continuous flocs. Increase the rotor speed to 35 rpm, perform the third pressurized mixing for 60 minutes, and extrude and granulate through a granulator to obtain alumina feed material.
[0083] Comparative Example 1
[0084] A method for preparing an alumina feed material (refer to Example 1 of Chinese patent CN113213896A), comprising the following steps:
[0085] (1) 81 wt% alumina ceramic powder is placed in a pressure mixer for preheating (140-220°C, 0.5-2h), and the alumina powder is dried until the water content is less than 0.5%;
[0086] (2) Then, a surfactant (stearic acid 0.28 wt%) was added to react with the alumina powder and then coat the surface of the alumina powder;
[0087] (3) adding a binder (2.42 wt% of high melt index polypropylene, 2.2 wt% of low melt index polypropylene, 0.17 wt% of high melt index polyethylene, 1.7 wt% of medium-high melt index polyethylene, 2.9 wt% of low melt index polyethylene, 0.5 wt% of ethylene-vinyl acetate copolymer, 0.34 wt% of ethylene-ethyl acrylate copolymer, 8 wt% of 58# semi-refined paraffin wax);
[0088] (4) After the binder is melted and the feed material is in a muddy state, add the formulated amount of plasticizer (oleic acid 0.28wt%);
[0089] (5) When the current reading on the mixer current display screen shows that the current reading is stable, add the formulated amount of emulsifier (SP600.21wt%), the mixing temperature is 165-220°C, the speed is 16-60rpm, and the mixing is repeated 1-4 times, each mixing time is 0.5-3h, and the mixture is mixed and mixed.
[0090] Comparative Example 2
[0091] A method for preparing a ceramic plastic-based alumina feed with a high catalytic degreasing rate (refer to Chinese patent CN113387691A), comprising the following steps:
[0092] (1) In anhydrous alcohol with an equal volume to that of alumina ceramic powder, add oleic acid (2% by mass of the binder), pour in the alumina ceramic powder, stir for 30 minutes, and bake in an oven at 60°C to evaporate the alcohol;
[0093] (2) After the temperature of the internal mixer is raised to 200°C, pour in the dried alumina ceramic powder, the binder (POM accounts for 80%, PP / PE accounts for 12%, EVA accounts for 5%, and wax accounts for 3%), zirconium oxide and alumina. After internal mixing into a mass, continue to internal mixing for 15 minutes. After internal mixing and granulation, the ceramic plastic-based alumina feed is obtained.
[0094] Comparative Example 3
[0095] The difference between Comparative Example 1 and Example 1 is that after the alumina ceramic powder is preheated, the solid modifier, the skeleton agent, the shape retaining agent and the lubricant are directly mixed with the preheated alumina ceramic powder and kneaded at 185° C. for 90 minutes.
[0096] Comparative Example 4
[0097] The difference from Example 1 is that after the alumina ceramic powder is preheated, the skeleton agent is first added for the first mixing, then the shape retaining agent, lubricant and liquid modifier are added for the second mixing, and finally the solid modifier is added for the third mixing.
[0098] Application Examples
[0099] An alumina ceramic product is made by a ceramic powder injection molding process, comprising the following steps:
[0100] (1) Injection molding: The mold shrinkage ratio was designed according to the shrinkage ratio of 1.200, and the alumina feedstocks prepared in the above-mentioned embodiments were respectively injected through a Nissin 110T injection molding machine, wherein the temperatures of each section of the injection molding machine were set at 190° C., 185° C., 180° C., 175° C., and 170° C., the injection peak pressure was 170 MPa, the holding pressure was 135 MPa, the cooling time was 15 s, and the mold temperature controller was 80° C. to prepare injection blanks, and the surface of the injection blanks had no flow lines, cracks, or deformation;
[0101] (2) Degreasing: In an oxalic acid degreasing furnace, the first degreasing was performed for 120 min, the second degreasing was performed for 500 min, and the third degreasing was performed for 120 min. The furnace temperature was 130° C., the fan speed was 35%, the air intake was 18 L / min, and the oxalic acid intake in each degreasing stage was set to 1.0 g / min, 3 g / min, and 2 g / min, respectively. After the catalytic degreasing was completed, the mass difference before and after the degreasing sample was weighed, and the degreasing rate was calculated. The degreasing rate was 14.3-14.5%, which met the standard (limit 15.3%).
[0102] (3) Sintering: In a high-temperature box-type sintering furnace (model FML-42 / 17), the temperature is raised from room temperature to 550°C for 11 hours and kept for 2 hours, then raised to 1300°C for 9 hours, and finally raised to 1630°C for 10 hours and kept for 2 hours, and then naturally cooled to obtain alumina ceramic products.
[0103] Product effect testing
[0104] The alumina feedstocks prepared in the above-mentioned embodiments and comparative examples were injection molded, degreased and sintered to obtain alumina ceramic standard parts. The performance of the alumina feedstocks and alumina ceramic products was tested, and the results are shown in Table 1.
[0105] Table 1 Performance test results of alumina ceramic standard parts obtained from alumina feedstocks of various embodiments and comparative examples
[0106]
[0107]
[0108] In the prior art, the melt flow rate of unmodified alumina feedstock is 90-300g / 10min, and the feed shrinkage rate OSF is about 1.200. When the powder loading reaches 82%, the mixing turns yellow and decomposes. As can be seen from the above table, when the powder loading of the present invention is as high as 82%, the density of the ceramic product made of the alumina feedstock of the present invention can reach 3.92-3.95g / cm 3 The melt flow rate reaches 500-1400g / 10min, and the shrinkage rate does not exceed 1.208%. It has the characteristics of high density, high melt flow rate and low shrinkage rate. It does not turn yellow during mixing and does not decompose. The bending strength of the obtained alumina ceramic standard parts is not less than 310±20MPa, and the hardness is not less than 1720kgf / mm 2 It is proved that the present invention improves the fluidity of alumina feed material (melt flow rate is not less than 500g / 10min) by improving the formula and preparation process of alumina feed material, and the product performance after sintering is good, the injection fluidity is good, the dimensional accuracy is good, and the process energy consumption is low, safe, environmentally friendly, stable and efficient.
[0109] Although Comparative Example 1 also adopts the method of adding various types of binders in steps, and adds paraffin wax which plays a key role in promoting flow, a variety of other modifiers are added while adding paraffin wax, such as high melt index polypropylene, high melt index polyethylene, ethylene-vinyl acetate copolymer, etc., which have a thickening effect on paraffin wax and are not conducive to improving fluidity. In addition, before adding paraffin wax, a surfactant is also added to the system, which is compatible with paraffin wax and does not play a role in enhancing shape retention. Moreover, the alumina feed obtained in Comparative Example 1 needs solvent extraction after injection molding, degreasing and then drying, and the sintering cycle is long, the steps are cumbersome, and the production cost is increased.
[0110] In Comparative Example 2, oleic acid is first used to modify the alumina ceramic powder. The oleic acid plays a depolymerization role. Subsequently, a binder, zirconium oxide, alumina and other substances are added and mixed together. The components in the formula do not function in an orderly manner, resulting in a large shrinkage rate, inability to ensure sintered dimensional stability, and low product yield.
[0111] In Comparative Example 3, the solid modifier, skeleton agent, shape retaining agent, and lubricant were directly mixed with the preheated alumina ceramic powder, and only one mixing was performed. Because the solid modifier that plays the role of wetting the surface of the ceramic powder did not play the initial role under the high powder loading setting, the inorganic powder and the organic binder were separated from each other, and the components inside the feed were decomposed after a long period of intense friction during mixing. At this time, the internal components of the feed were uneven, and hidden cracks were prone to occur during the later degreasing and sintering, and the performance dropped sharply.
[0112] In Comparative Example 4, the order of adding the binder is reversed. Since the low-melting-point oleic acid added first volatilizes and decomposes severely when heated, it is easy to rot and deteriorate, has lost its modifying effect and increases the harm to the human body. At the same time, the stearic acid added later cannot be effectively integrated into the agglomerated feed, resulting in poor feed fluidity.
Claims
1. A method for preparing an alumina feed, characterized in that: The raw materials for preparing the alumina feedstock are alumina ceramic powder and a binder, and the binder is a solid modifier, a skeleton agent and a shape retaining agent; The method for preparing the alumina feed material comprises the following steps: (1) Alumina ceramic powder and a solid modifier are mixed and kneaded for the first time to obtain material A; (2) mixing the material A obtained in step (1) with the skeleton agent, and performing a second mixing process to obtain material B; (3) mixing the material B obtained in step (2) with a shape retaining agent, performing a third mixing process, and granulating to obtain the alumina feed material; In step (1), before mixing the alumina ceramic powder and the solid modifier, the alumina ceramic powder is preheated, the preheating temperature is 120-140° C., and the preheating time is 15-45 minutes; In step (3), the temperature of the third mixing is 180-190° C., and the time of the third mixing is 60-80 min; The mass of the solid modifier accounts for 1-3% of the total mass of the binder; The mass of the skeleton agent accounts for 9-11% of the total mass of the binder; The mass of the shape retaining agent accounts for 75-91% of the total mass of the binder; The mass of the binder accounts for 15-30% of the total mass of the alumina feed; The particle size of the alumina ceramic powder is 0.8-1 μm; The alumina ceramic powder is a non-spherical powder; The solid modifier is stearic acid; The skeleton agent is polypropylene and / or polyethylene; The shape retaining agent is polyoxymethylene.
2. The preparation method according to claim 1, characterized in that: In step (1), the temperature of the first mixing is 180-190° C., and the time of the first mixing is 1-10 min.
3. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the second mixing is 180-190° C., and the time of the second mixing is 10-30 min.
4. Alumina feed material obtained by the preparation method according to any one of claims 1 to 3, characterized in that: The alumina feed has a melt flow rate of 500-1400 g / 10 min at 190° C. and 21.6 kg.
5. Application of the alumina feed material according to claim 4 in the fields of aerospace, new energy or semiconductor.
6. An alumina ceramic product, characterized in that: The raw materials for preparing the alumina ceramic product include the alumina feed material according to claim 4.
Citation Information
Patent Citations
Feed for aluminum oxide ceramic injection molding and feed injection molding method
CN113213896A
Ceramic plastic-based feed with high catalytic degreasing rate and preparation method thereof
CN113387691A
Method for producing orthodontic self-ligating tooth bracket through powder injection molding
CN108213439A
Preparation method of titanium alloy injection feed for injection molding
CN114210980A